DUSP6 mediates T cell receptor-engaged glycolysis and restrains T FH cell differentiation - Wei-Chan Hsu; Ming-Yu Chen; Shu-Ching Hsu; Li-Rung Huang; Cheng‐Yuan Kao; Wenhui Cheng; Chien-Hsiung Pan; Ming-Sian Wu; Guann‐Yi Yu; Ming‐Shiu Hung; Chuen-Miin Leu; Tse‐Hua Tan; et al. (2018)
Significance Naive T cells at quiescent state utilize mitochondrial respiration to generate ATP. In response to antigen, activated T cells through T cell receptor (TCR) and CD28 differentiate to T H 1, T H 2, or T H 17 effector cells with an induction of aerobic glycolysis. Here, we demonstrate a role for DUSP6 in the glycolysis commitment during T cell activation. DUSP6 deficiency prompts activated T cells to rely on glucose-independent fuels. We show that DUSP6 fine-tunes TCR-MAPK signaling, which determines follicular helper T (T FH ) effector-cell differentiation regardless of a glycolytic defect. Our findings imply that glycolysis is required for survival of activated T cells but optional for IL-21 production in T FH cell differentiation.